2013
DOI: 10.1111/ecc.12041
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of Life: patient perceptions of expressive therapy during chemotherapy sessions

Abstract: Through a quanti-qualitative study, we observed the effects of group expressive therapy (ET) sessions on patients' feelings and sense of well-being, as part of the Infusion of Life project. This project is part of a broader programme to improve integral care, developed by an interdisciplinary team headed by a medical doctor who is also an artist and expert in ET. We offered 48 group ET sessions to a total of 253 outpatients with cancer or autoimmune disorders receiving venous infusions in the chemotherapy room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…; Vianna et al . ), and findings from the current study add further explanations to this body of literature. However, this is only one aspect of how creative expression is used in art therapy.…”
Section: Implications For Practitionerssupporting
confidence: 80%
See 4 more Smart Citations
“…; Vianna et al . ), and findings from the current study add further explanations to this body of literature. However, this is only one aspect of how creative expression is used in art therapy.…”
Section: Implications For Practitionerssupporting
confidence: 80%
“…This study adds to the rich body of literature that has revealed how art helps adults (e.g. Collie et al 2006;Vianna et al 2013) and adolescents (e.g. Baerg 2003) express and explore emotions and cognitions related to their cancer journeys.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations